Does Exchange Rate Matter in Profitability of Listed Companies in South Africa? An Empirical Approach - Yeboah, Michael; Takacs, Andras (International Journal of Energy Economics and Policy, 2019)
Exchange rate fluctuation is phenomenal in South Africa. This study thus estimates the impact of exchange fluctuation on the profitability of listed mining and manufacturing companies over 2000-2014. The study controlled for company level factors including liquidity, leverage, firm size, tangibility, the opportunity for growth and interest cover. The macroeconomic factors controlled for were interest rate and economic growth. The study used random effect model for estimation. Profitability was measured as return on asset. Exchange rate fluctuation had a significant negative impact on return on the asset when both industries are considered. However, exchange rate fluctuation had no significant impact on return on the asset in the mining industry but in the manufacturing industry. Liquidity, Interest cover, and tangibility had a significant positive impact but leverage had a significant negative impact on return on asset. At the macro level, interest rate had a significant positive impact but economic growth had no significant impact on return on asset. The study recommends that managers of manufacturing companies should adopt strategies such as currency swaps, future contract, and hedging to avert exchange rate fluctuation risk. Keywords: Exchange Rate; mining companies; Profitability; South Africa JEL Classifications: F41; L72; L25; O55 DOI: https://doi.org/10.32479/ijeep.8208